Novel temperature responsive polymer based sealant for embolization - Ali E. Dabiri; Ravin Narain; Yi-Yang Peng; Wenda Wang; Max Itkins; Ghassan S. Kassab (Science and Technology of Advanced Materials)
A sealant has been developed that improves upon current catheter-based treatments in the following ways: 1) Efficient delivery system, 2) No in situ polymerization, 3) No harmful byproducts, and 4) Cost-effective formulation. During the development process, particular attention was given to materials that were tunable, safe, and effective sealant agents. The thermo-responsive properties of poly(N-isopropylacrylamide) (PNIPAM) provides an ideal foundation to develop an optimized solution. Through a combination of model-based and material testing, a hydrogel was developed that balances conformational factors to achieve a customized transition temperature, radiopacity suitable for visualization, mechanical properties suitable for delivery via 3Fr catheter, sufficient cohesion once applied to resist migration under physiological pressures and an improved safety profile. Two applications, embolization of lymphatic leakage and exclusions of the left atrial appendage (LAA), to eliminate LAA dead space to reduce the risk of thromboembolic events, were considered. The material and benchtop results for this product demonstrate the suitability of this new material not only for these applications but also for other potential healthcare applications.